ANALYSING THE SPATIO-TEMPORAL CHANGES OF LANGH AND DRIGH LAKES DUE TO ANTHROPOGENIC ACTIVITIES USING GIS AND REMOTE SENSING TECHNIQUES - Sadia Allah Ditta; Tayyaba Suhail; Altaf Ali Siyal; Kamran Ansari (Earth Sciences Pakistan, 2021)
Ramsar sites are important habitats for the locals as well as for migratory birds that visit these sites across the borders every year. Langh and Drigh lakes were selected as the study area for this research. Drigh Lake is one of the important Ramsar sites, and Langh Lake is an important wildlife sanctuary of national importance. For the past few decades, these lakes are degrading due to anthropogenic activities. To quantify these variations, present study was carried out to detect the land use and land cover change in these lakes and their surrounding areas from 1988 to 2020. Level-2 imageries of Landsat 5, 7, and 8 were downloaded and analyzed using hybrid classification, and results were mapped in ArcMap. Accuracy assessment of the results of selected years was done to check the accuracy of results using the Kappa coefficient. Kappa coefficient resulted between 0.82 and 0.95 for this study. Classification results depicted a significant increase in the vegetation area which is 72% and 32% for langh and drigh lakes respectively since 1988. Results show an increase in the buildup area and a decrease in the barren land. The presence of dense vegetation in the lakes near their boundaries verifies encroachment of lakes by the local farmers.